2018
DOI: 10.1101/265611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Live cell monitoring of double strand breaks inS. cerevisiae

Abstract: We have used two different live-cell fluorescent protein markers to monitor the formation and localization of double-strand breaks (DSBs) in budding yeast. Using GFP derivatives of the Rad51 recombination protein or the Ddc2 checkpoint protein, we find that cells with three site-specific DSBs, on different chromosomes, usually display 2 or 3 foci that coalesce and dissociate. Rad51-GFP, by itself, is unable to repair DSBs by homologous recombination in mitotic cells, but is able to form foci and allow repair w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 61 publications
(72 reference statements)
2
12
0
Order By: Relevance
“…Disrupting microtubules with nocodazole or creating MT-related mutations impairs the normal increase in local Rc after damage and blocks the motion of DSB ends to which the Ddc2-GFP protein binds [81]. …”
Section: Changes In Chromosome Mobility May Facilitate Homology Searcmentioning
confidence: 99%
See 1 more Smart Citation
“…Disrupting microtubules with nocodazole or creating MT-related mutations impairs the normal increase in local Rc after damage and blocks the motion of DSB ends to which the Ddc2-GFP protein binds [81]. …”
Section: Changes In Chromosome Mobility May Facilitate Homology Searcmentioning
confidence: 99%
“…This is especially evident when the reporter of multiple breaks is a fluorescent version of Rad52; however, when immunofluorescence was used to probe spread chromatin from lysed cells, three HO-induced DSBs yielded three foci of both Rad51 and Rad52 [94]. Recently, we monitored multiple, separate DSBs in live cells using two different GFP-marked probes: the checkpoint protein, Ddc2-GFP or a Rad51-GFP fusion protein that forms foci and is able to complete DSB repair when wildtype Rad51 is also present [81]. In cells with 3 HO-induced DSBs on different chromosomes, about 30% of cells have a single Rad51 or Ddc2 fluorescent focus with the intensity expected for all three individual foci grouped in one location.…”
Section: Are There “Repair Centers” When There Are Multiple Dsbs?mentioning
confidence: 99%
“…mCherry was fused to Mre11, Smc5, Rfa1, Slx5, and Rad51 with a linker sequence integrated between the protein and C-terminal mCherry tag (Mre11, Smc5, Slx5, and Rad51: GGSGGS, Rfa1: AAAAAAAAG). For Rad51-mCherry a plasmid expressing Rad51 under its own promoter was also transformed into the strain; the plasmid is the same one used in Waterman et al, 2019 and the complemented strain shows a slight MMS sensitivity as previously published ( Figure S2). X. Zhao Lab strains used are listed in Table S9 and were isogenic to W1588-4C, a RAD5 derivative of W303 (MATa ade2-1 can1-100 ura3-1 his3-11,15 leu2-3, 112 trp1-1 rad5-535).…”
Section: Methods Detailsmentioning
confidence: 99%
“…Rad51 fusions are known to affect protein function, but it was recently shown that a Rad51-GFP fusion was non-functional but also not dominant negative; the repair functionality of both an induced DSB or MMSinduced damage could be complemented by the addition of WT Rad51 protein expressed from a plasmid, and the formation and disappearance of Rad51 foci paralleled the kinetics of repair as in WT cells (Waterman et al, 2019). We tested the MMS sensitivity of the complemented Rad51-mCherry construct in our strain background and found only a slight sensitivity in line with what was reported for Rad51-GFP + Rad51 (Waterman et al, 2019) ( Figure S2). The co-localization of each protein with the CAG repeat (marked with GFP at the nearby LacO array) was assessed, and whether the co-localization was occurring at the nuclear periphery (NP) or not was scored ( Figure 5A).…”
Section: Differential Timing Of Mre11 Smc5 Rfa1 Slx5 and Rad51 Asmentioning
confidence: 99%
“…For all AID tagged experiments, 500 µM of 3-Indoleacetic acid (IAA) (Sigma Aldrich) was added to cultures 2 h after galactose addition. Adaptation assays were carried out as previously described (17,58). Briefly, cells were grown overnight in YEP-Lac and plated in YEP-Lac agarose plates containing 2% galactose.…”
Section: Media Strains and Adaptation Assaysmentioning
confidence: 99%